The current status of inguinal lymph node dissection for penile cancer in P R of China - Du, Jiang-Ping; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2018)
With the advancement of technology, the inguinal lymph node dissection for penile cancer has developed rapidly. In this paper, the literature published and indexed on CNKI was searched in the past 10 years. The current status of inguinal lymph node dissection for penile cancer was described in terms of surgical trends, timing of surgery, surgical methods, and surgical decision-making.